Assessment of Local Pesticides Used by Farmers in Jorhat District - Gogoi, Bijit (International Journal of Scientific Research in Biological Sciences, 2025)
The indiscriminate use of chemical pesticides has raised concerns about environmental degradation, human health risks, and the sustainability of agricultural practices worldwide. In the context of Jorhat District, Assam, local farmers rely on both chemical and traditional pesticides to combat pests and ensure crop productivity. The aim of this research is to determine the types, usage patterns, and impacts of local pesticides applied by farmers in five selected villages: No.2 Sonari Gaon, Sotai Bhakat Gaon, Kakojan (Bonpithaguri village), Sokai Khongiya Gaon, and Garumora. Data were collected through field surveys, structured interviews, and questionnaires filled by 100 farmers across the study sites.